INTERACTION PATTERNS IN ENGLISH AS FOREIGN LANGUAGE CLASSROOM AT LOWER SECONDARY SCHOOLS - Hanna Sundari; Zainal Rafli; Sakura Ridwan (English Review: Journal of English Education, 2017)
Interaction plays an important role in language learning process in classroom setting. This present study aims at investigating the patterns used in classroom interaction by English lower secondary teachers. Using qualitative approach, this study was carried out in eight lower secondary schools (SMP) in Jakarta. Moreover, twenty English language experienced teachers with three to thirty-six years of teaching experiences were recruited as participants. Interviews, classroom observations/recording and focus-group discussion were instruments to collect data. For analyzing the data, qualitative data analysis was selected in developing categories and sub-categories of the data. The findings showed that the teachers apply at least three identified interactional patterns in EFL classroom in which modify the IRF structure. Teachers initiate interaction to the entire class (T-whole class interaction) by giving questions and instruction. Then, they also point out one specific student to answer the question or do the required task (Teacher fronted student interaction). In addition, teachers set the classroom activity to make the students interact each other (student-student interaction). Moreover, the student responses and other interactional features identified in language classroom are also discussed.Keywords: interaction patterns, EFL classrooms, secondary school